Immunoreactivity of Tissue Plasminogen Activator and of Its Inhibitor Complexes - Rånby, M; Nguyen, G; Scarabin, P Y; Samama, M (Thrombosis and Haemostasis, 1989)
An enzyme linked immunosorbent assay (ELISA) based on goat polyclonal antibodies against human tissue plasminogen activator (tPA) was evaluated. The relative immunoreactivity of tPA in free form and tPA in complex with inhibitors was estimated by ELISA and found to be 100, 74, 94, 92 and 8l% for free tPA and tPA in complex with PAI-1, PAI-2, α2-antiplasmin and C1-inhibitor, respectively. Addition of tPA to PAI-1 rich plasma resulted in rapid and total loss of tPA activity without detectable loss of ELISA response, indicating an immunoreactivity of tPA in tPA/PAI-1 complex of about l00%. Three different treatments of citrated plasma samples (acidification/reneutralization, addition of 5 mM EDTA or of 0.5 M lysine) prior to determination by ELISA all resulted in increased tPA levels. The fact that the increase was equally large in all three cases along with good analytical recovery of tPA added to plasffi, supported the notion that all tPA antigen present in plasma samples is measured by the ELISA. Analysis by ELISA of fractions obtained by gel filtration of plasma from a patient undergoing tPA treatment identified tPA/inhibitor complexes and free tPA but no low molecular weight degradation products of tPA. Determinations of tPA antigen were made at seven French clinical laboratories on coded and randomized plasma samples with known tPA antigen content. For undiluted samples there was no significant difference between the tPA levels found and those known to be present. The between-assay coefficient of variation was 7 to 10%. In conclusion, the ELISA appeared suited for determination of total tPA antigen in human plasma samples.
Keywords: Tissue plasminogen activator; tPA; Immunoreactivity; Immunological determination; Elisa; Multicenter validation